Noninvasive methods for the assessment of photoageing. (21st February 2013) - Wheller, Laura; Lin, Lynlee L; Chai, Eric; Sinnya, Sudipta; Soyer, H Peter; Prow, Tarl W
Abstract: Although histopathological dermal elastosis is the current gold standard for the diagnosis of photoageing, noninvasive methods for quantifying the amount of photodamage to skin are clearly preferable. This study is the first to survey five noninvasive methods of assessing photoageing (clinical examination, spectrophotometry, skin surface topography, reflectance confocal microscopy and fluorescence lifetime imaging microscopy) in the same individual. Measurements for each noninvasive method were compared across nine individuals from three participant groups ('younger', 'older' and 'photodamaged') in UV‐protected volar and UV‐exposed dorsal forearm skin. Overall, participants in the younger group had the lowest measures of photodamage, while those in the photodamaged group had the highest, as indicated by each modality. The five noninvasive strategies surveyed in this study may demonstrate potential as a suitable methodology for the quantification of photoageing. The advantage of such noninvasive methods is that they allow for skin visualisation in vivo and repeated assessments of the same site. The main limitation of this study was its small sample size, which may have precluded many findings of statistical significance.